Quality of life, self-stigma, and coping strategies in patients with neurotic spectrum disorders: a cross-sectional study - Holubova, Michaela; Prasko, Jan; Ociskova, Marie; Kantor, Kryštof; Vanek, Jakub; Slepecky, Milos; Vrbova, Kristyna (Psychology research and behavior management, 2019)
BACKGROUND: Modern psychiatry focuses on self-stigma, coping strategies, and quality of life (QoL). This study looked at relationships among severity of symptoms, self-stigma, demographics, coping strategies, and QoL in patients with neurotic spectrum disorders. METHODS: A total of 153 clinically stable participants who met criteria for generalized anxiety disorder, social phobia, panic disorder, agoraphobia, mixed anxiety-depressive disorder, adjustment disorders, somatoform disorders, or obsessive-compulsive disorder were included in a cross-sectional study. Psychiatrists examined patients during regular psychiatric checkups. Patients completed the Quality of Life Satisfaction and Enjoyment Questionnaire (Q-LES-Q), Internalized Stigma of Mental Illness Scale (ISMI), a sociodemographic questionnaire, the Stress Coping Style Questionnaire (Strategie Zvládání Stresu [SVF] 78), and the Clinical Global Impression (CGI) scale. RESULTS: The diagnostic subgroups differed significantly in age and use of negative coping strategies, but not in other measured clinical or psychological variables. The findings showed that neither sex nor partnership played a role in perceived QoL. All Q-LES-Q domains correlated negatively with all ISMI domains, except school/study. Unemployed and employed groups of patients differed in QoL. Each of the coping strategies, except the need for social support, was related to self-stigma. The findings showed that sex, partnership, education, and employment played no role in self-stigma. No differences between sexes in positive coping strategies, severity of disorder, self-stigma, or QoL were found. QoL correlated significantly with all coping strategies, except for guilt denial. Multiple regression showed the most important factors to be positive coping, employment, and overall self-stigma rating, explaining 32.9% of QoL. Mediation analysis showed self-stigma level and negative coping strategies to be the most influential. The most substantial factors associated with self-stigma, as indicated by regression analysis, were Q-LES-Q total, subjective CGI, and positive coping strategies, which clarified 44.5% of the ISMI. CONCLUSION: The study confirmed associations among self-stigma, quality of life, disorder severity, and coping strategies of outpatients with neurotic spectrum disorders.
Keywords: self-stigma; neurotic spectrum disorders; quality of life; coping strategies